WOMEN'S LAW REJECTS REFERENCE IN THE PERSPECTIVE OF ISLAMIC JURISPRUDENCE AND THE COMPILATION OF ISLAMIC LAW - Fatma, Fatma; Satrianingsih, Andi; Saleh, Muhammad; Hamzah, Nur Asia; Basri, St Risnawati (Journal of Family Law and Islamic Court, 2023)
This study used library research. The techniques used in this study include; Data collection, after the required data has been collected, then several stages are carried out, namely: Data reduction, display data, concluding.  After the process of data collection and data management has been completed, the next step is to analyze the data to get a complete picture related to the problem that is the object of research. This study discusses the issue of referencing, that is, legal reference is carried out without the consent of the wife, as long as she is still in  the period of 'iddah based on the agreement of the ulama.  Meanwhile, in the Compilation of Islamic Law, the legal reference is valid if it has received approval from the wife. From this problem, there are two formulations of problems that will be studied by the author in this study, namely: 1) How women's law rejects reference in the perspective of Islamic jurisprudence. 2) How women's law rejects references in the Compilation of Islamic Law. The objectives in this study are twofold, namely: 1) To know the law of women refusing to refer in the perspective of Islamic jurisprudence. 2) to know the law women refuse to refer to in the perspective of the Compilation of Islamic Law. Based on the results of this study, it can be concluded, namely: 1) In Islamic law, scholars agree that reference is the prerogative of the husband or the absolute right of the husband, so there is no need for consent from the wife. 2) Whereas in the Compilation of Islamic Law it is stated that if a husband is going to make a reference to his ex-wife must first obtain the consent of his ex-wife, and the wife has the right to object to the will of the reference.Keywords: Law, Women, Reference, Islamic Jurisprudence, Compilation of Islamic LawPenelitian ini menggunakan penelitian riset kepustakaan (library research). Adapun teknik yang digunakan dalam penelitian ini antara lain; Pengumpulan data, setelah data yang diperlukan telah terkumpul, kemudian dilakukan beberapa tahapan yaitu: Reduksi data (data reduction), display data, concluding. Setelah proses pengumpulan data dan pengelolahan data telah selesai, maka selanjutnya adalah menganalisis data guna mendapat sebuah gambaran utuh terkait dengan permasalahan yang menjadi objek penelitian. Penelitian ini membahas tentang masalah rujuk, yaitu rujuk sah dilakukan tanpa persetujuan istri, selama dia masih dalam masa ‘iddah berdasarkan kesepakatan ulama. Sedangkan dalam Kompilasi Hukum Islam, rujuk sah hukumnya apabila sudah mendapat persetujuan dari pihak istri. Dari permasalahan ini, ada dua rumusan masalah yang akan dikaji penulis dalam penelitian ini, yaitu: 1) Bagaimana hukum wanita menolak rujuk dalam perspektif fikih Islam. 2) Bagaimana hukum wanita menolak rujuk dalam Kompilasi Hukum Islam. Tujuan dalam penelitian ini ada dua, yaitu: 1) Untuk mengetahui hukum wanita menolak rujuk dalam perspektif fikih Islam. 2) untuk mengetahui hukum wanita menolak rujuk dalam perspektif Kompilasi Hukum Islam. Berdasarkan dari hasil penelitian ini dapat disimpulkan yaitu: 1) Dalam hukum Islam, ulama sepakat bahwa rujuk merupakan hak prerogatif suami atau hak mutlak suami, sehingga tidak diperlukan adanya persetujuan dari pihak istri. 2) Sedangkan dalam Kompilasi Hukum Islam disebutkan bahwa apabila seorang suami akan melakukan rujuk terhadap mantan istrinya terlebih dahulu harus mendapat persetujuan dari mantan istrinya, serta istri berhak mengajukan keberatan atas kehendak rujuk tersebut.Kata Kunci: Hukum, Wanita, Rujuk, Fikih Islam, Kompilasi Hukum Islam